2021
DOI: 10.1088/1361-6668/ac216a
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the superconducting properties of NbN films deposited by DC magnetron sputtering on a high-k dielectric HfO2 buffer layer

Abstract: The influence of the buffer layer of hafnia dielectric (HfO 2 ) on superconducting properties of niobium nitride films (NbN), produced by the technique of the reactive magnetron depositing has been investigated for the first time. This study presents a comprehensive analysis of morphological, microstructural, and electrophysical parameters of thin NbN films. The dependence of transition critical temperature from the thickness of the HfO 2 buffer layer has been obtained. For the first time, it has been demonstr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Magnetron sputtering is a physical vapor deposition (PVD) technique, and it is reportedly the most widely used method for preparing NbN thin films [6,[18][19][20]. In the mature magnetron sputtering deposition process, it has been found that various process conditions, such as the substrate material, the substrate temperature, the nitrogen partial pressure (nitrogen content), the radio frequency bias, and the deposition thickness, can affect the structure and superconducting properties of the films.…”
Section: Magnetron Sputtering Depositionmentioning
confidence: 99%
“…Magnetron sputtering is a physical vapor deposition (PVD) technique, and it is reportedly the most widely used method for preparing NbN thin films [6,[18][19][20]. In the mature magnetron sputtering deposition process, it has been found that various process conditions, such as the substrate material, the substrate temperature, the nitrogen partial pressure (nitrogen content), the radio frequency bias, and the deposition thickness, can affect the structure and superconducting properties of the films.…”
Section: Magnetron Sputtering Depositionmentioning
confidence: 99%
“…Also, it found that the work under the NbN superconducting critical temperature T c with range of 40 to 5 K depending on thickness of the film as well as its quality and substrate of suitable (growth of epitaxial as well as crystal of single) (Slysz et al , 2011). In addition, properties of a superconductor were studied for NbN thin films prepared via magnetron sputtering (DC) using high-k dielectric HfO 2 like buffer layer (Porokhov et al , 2021; Chockalingam et al , 2008) using MgO (100) substrate that it has crystalline of single below many conditions using magnetron sputtering (influence of power and ratio of nitrogen gas).…”
Section: Introductionmentioning
confidence: 99%